Students’ perceptions of using padlet as a learning tool for English writing / Mohd Zaidi Mahmud - Mahmud, Mohd Zaidi (Universiti Teknologi MARA, Kedah, 2019)
The introduction of Padlet as a learning tool has changed the traditional method of teaching from teacher-centered to student-centered. This can be seen in the classes where the lecturers have integrated Padlet in their teaching, particularly in English writing class. In this study, Padlet was used as a tool or platform for learning English writing. The aim of this study is to investigate the students’ perceptions of the usage of Padlet in learning English writing in the English as Second Language (ESL) tertiary classroom. A total of 60 students from one private college in Penang were asked to complete a survey questionnaire, and 6 of them were interviewed to gather feedback on their perceptions of using Padlet as a learning tool for English writing. The survey results showed that Padlet is a good learning tool for college students with a mean score of 3.503 (S.D=0.476). The interview analysis showed clearer results. Based on the focus group interview, the students think that Padlet could not assist them to learn English writing, as Padlet only accommodate simple English activities. They have suggested that by adding advanced English programs and activities into Padlet, it will help them to improve the learning process of English writing.